Avaliação do efeito da água ozonizada em diferentes concentrações em biofilmes de Candida albicans – estudo in vitro - Basso, Sabrina (2022)
This study aimed to compare the antimicrobial action of ozonized water (OA) at concentrations 43 and 70 µg/mL, to 2.5% sodium hypochlorite (NaOCl) on C. albicans biofilm. After biofilm formation on polystyrene plates, the following couting methodologies were applied: Colony Forming Units (CFU), quantification of biomass by crystal violet (CV), determination of metabolic activity and evaluation of gene expression by qRT-PCR. The CFU count showed a reduction of 93.7% and 98.5% for AO 43 and 70 µg/mL and 99.9% for NaOCl. The biomass reduction was 71.8% for NaOCl, and for AO concentrations in order of 66% for both. About viability, there was a reduction of 43.3% and 58.3% for AO at concentrations 43 and 70 μg/mL, and 83.7% for NaOCl. The qRT-PCR data demonstrated a small decrease in the expression of the genes als3, bcr1, hwp1 and cph1, for als3 there was a reduction of 4.2%, bcr1 3.1%, hpw1 9.7% and cph1 7.8%. Finally, AO and NaOCl were effective in reducing the biofilm of C. albicans, however the effectiveness of AO was lower than NaOCl, suggesting that ozone can be used as an adjuvant for biofilm removals.